Assessment of the performance of warm mix asphalts in road pavements - Silva, Hugo Manuel Ribeiro Dias da (2010)
Several processes and products are available to produce warm mix asphalt (WMA). These may reduce the mixing and compaction temperatures in relation to hot mix asphalt (HMA), ensuring the necessary performance in the pavement. Lower plant mixing temperatures mean reduction in fuel consumption and lower emissions, what may contribute to diminish health and odour problems and to decrease costs. During this work, two commercial additives (Sasobit® and Cecabase®) were used to produce WMAs, which were compared with a conventional HMA. Initially, the mixtures were designed, the amount of additive was selected (based on the binder characterization) and the mixing temperatures of the WMAs were chosen by means of EN 12697-10 compactability comparison. Then, a road trial was built and test specimens were collected (both of HMA and WMAs) for volumetric composition and mechanical behaviour assessment. This study essentially provides a better understanding of the good performance capabilities of WMA mixtures.